Performance analysis of video traffic over MPLS-TE with Diffserv / Maisarah Ismail - Ismail, Maisarah
At present, Service Providers (SP) are in the midst of evaluating and evolving their various networks to a single converged Internet Protocol (IP) -based network infrastructure which able to use the existing and future services. Despite of having many options proposed, it is still a challenging task to implement Quality of Service (QoS) in IP based network. Differentiated Services (DiffServ) as one of the QoS mechanism, has become the mainstream of QoS solution. With DiffServ mechanism, traffic can be classified based on the priority to provide quality of service in order to meet the Service Level Agreement (SLA). Multi-Protocol Label Switching (MPLS) with Traffic Engineering (TE) complements DiffServ mechanisms to perform better in providing QoS architecture. This paper discussed and analyzed performance of video traffic over MPLS Traffic Engineering (TE) with DiffServ using a set of traffic model for video and data. Four different network scenarios were chosen which include different type of scheduling mechanism in QoS application. Performance parameters such as end to end delay, throughput, and Packet Delay Variation (PDV) were compared and analyzed. The comparative study showed that Priority Queuing (PQ) has generally improved the performance of video traffic compared to MPLS-TE only network and other type of scheduling mechanism.